Autonomic nervous system modulation by G protein-biased mu-opioid receptor agonists: A translational scoping review protocol - Yi Zhang; Qiuxiang Chen; Yuanyuan Zhou; Qingjun Zeng; Haishan Cui; Yukai Zhou (PLoS ONE, 2026)
Background G protein-biased mu-opioid receptor (MOR) agonists such as oliceridine and tegileridine were developed to reduce opioid-related side effects while keeping analgesic efficacy. The US FDA approved oliceridine in 2020 and China NMPA approved tegileridine in January 2024. Clinical development mainly focused on respiratory depression and gastrointestinal problems, but little attention has been paid to the autonomic nervous system (ANS) effects of these drugs. Traditional opioids change heart rate variability (HRV) and sympathovagal balance mainly through central mechanisms. It is not clear whether biased agonists show different autonomic profiles compared with traditional opioids. There is an ongoing scientific debate about whether the benefits of these drugs come from true signaling bias or from low intrinsic efficacy. Methods We will conduct a scoping review following JBI methodology and report according to PRISMA-ScR guidelines. We will search PubMed, Embase, Web of Science and Cochrane Library from database start to March 2026. FDA and NMPA regulatory documents will also be searched. Two reviewers will screen studies and extract data independently. We will include in vitro cellular assays, in vivo animal experiments, and clinical studies examining oliceridine, tegileridine or other biased MOR agonists that report cardiovascular or autonomic outcomes. Results will be organized in an Evidence Matrix by drug, evidence level and measurement timepoint. Animal studies will be stratified by anesthetic state (conscious versus anesthetized). Discussion We will map the evidence against three mechanistic paradigms: that biased agonism preserves autonomic homeostasis; that observed benefits come from partial agonism rather than signaling bias; or that no meaningful autonomic differences exist between biased and traditional agonists. This review will map evidence gaps and inform future clinical trial design with autonomic endpoints. We note that tegileridine has much less published data than oliceridine, and this gap analysis will help set research priorities. Protocol registration: Open Science Framework (OSF) [ https://doi.org/10.17605/OSF.IO/N2XZC ].